2023
DOI: 10.32471/exp-oncology.2312-8852.vol-42-no-2.14632
|View full text |Cite
|
Sign up to set email alerts
|

Expression of micro-RNA hsa-miR-30c-5p and hsa-miR-138-1 in renal cell carcinoma

Abstract: Summary. Aim: To analyze the expression levels of hsa-miR-30c-5p and hsa-miR-138-1 in tumors of patients with renal cell carcinoma to determine whether they could be used as diagnostic markers. Materials and Methods: The relative expression of hsa-miR-30c-5p and hsa-miR-138-1 was compared in the paired samples of kidney tumor tissue and conventionally normal tissue adjacent to the tumor. Results: We found a significant decrease in miR-30c-5p and miR-138-1 levels in tumor tissues even in the cases of early stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…However, the possible role of miR-30c-5p as a biomarker for early diagnosis or development of recurrence needs further investigation. miR-30c-5p studied here has been shown to be involved in other cancers such as colorectal cancer [32,33], non-small cell lung cancer [34,35], gastric cancer [36], pancreatic ductal adenocarcinoma [37], renal cell carcinoma [38,39], hepatocellular carcinoma [40][41][42][43], breast cancer [44][45][46][47][48], laryngeal cancer [49], and other malignancies. For example, in gastric cancer, miR-30c-5p suppresses migration, invasion, and epithelial to mesenchymal transition via targeting MTA1 [36].…”
Section: Discussionmentioning
confidence: 85%
“…However, the possible role of miR-30c-5p as a biomarker for early diagnosis or development of recurrence needs further investigation. miR-30c-5p studied here has been shown to be involved in other cancers such as colorectal cancer [32,33], non-small cell lung cancer [34,35], gastric cancer [36], pancreatic ductal adenocarcinoma [37], renal cell carcinoma [38,39], hepatocellular carcinoma [40][41][42][43], breast cancer [44][45][46][47][48], laryngeal cancer [49], and other malignancies. For example, in gastric cancer, miR-30c-5p suppresses migration, invasion, and epithelial to mesenchymal transition via targeting MTA1 [36].…”
Section: Discussionmentioning
confidence: 85%
“… 23 In previous studies, the expression of miR-30c-5p was tissue specific, and it exerted both oncogenic and tumor-suppressing roles in different types of cancer. 13 , 14 , 16 , 17 It was reported that aberrant expression of miR-30c was a potential early diagnostic marker in HCC. 18 , 24 Meanwhile, miR-30c downregulation was associated with HCV core protein-induced EMT in HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Although miR-30c-5p is considered a potential diagnostic indicator, it has also been reported to act as a tumor promoter in various tumor types. 15 , 16 Inhibiting miR-30c-5p expression offers a possible treatment of isolinderalactone-induced apoptosis for triple-negative breast cancer. 17 A previous study showed that the expression profile of serum miR-30c-5p was found to be deregulated in hepatitis C virus (HCV)-positive HCC.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-30c-5p is involved in many biological events, including cell apoptosis, growth, and differentiation. In a recent study, decreased expression of miR-30c-5p was associated with an unfavorable course of the renal cell carcinoma [67]. MiR-130a-3p, a member of the miR-130 family, is an important regulator of tumor progression and metastasis [68].…”
Section: Discussionmentioning
confidence: 99%